Microstructure evolution of Ti-6Al-4V during superplastic-like forming - Guo, Mei-Ling (2015)
Superplastic-like forming is a recent developed sheet-forming process that combines hot drawing (mechanical pre-forming) with gas forming. It is an efficient way to form sheet metals into complex parts for automotive and aerospace industries. In comparison with conventional superplastic forming process, the forming time for superplastic-like forming can be significantly shortened as the hot-drawing step would have produced a pre-formed component before gas forming. The other advantage of the superplastic-like forming is its capacity for lower temperature forming, for which superplasticity is not possible. Non-superplastic grade Ti-6Al-4V sheets were successfully formed by superplastic-like forming at 800 °C in 16 min. The maximum percentage thinning of 54% occurred at the outward corners. In this paper, electron backscatter diffraction (EBSD) was used to examine the microstructure evolution of Ti-6Al-4V at different forming stages during superplastic-like forming process. Some small equiaxed grains, regarded as newly recrystallized grains, were observed near the deformed area after hot drawing. Grains became more randomly distributed as the recrystallization continued during gas forming stage. The as-received structures were finally replaced by the equiaxed grains with an almost random misorientation distribution after the forming process. Dynamic recrystallization was considered as the main deformation mechanism for the non-superplastic grade Ti-6Al-4V alloy.